Method for producing expandable polyamide resin particles and method for producing expanded polyamide resin particles
By impregnating inorganic physical foam into moisture-containing polyamide resin particles and heating them with hot air or steam, the method addresses the issue of uneven bubble diameters and low productivity in existing foamed polyamide-based resin production, achieving uniform and low-density foamed particles.
Patent Information
- Application Number
- JP2021132390
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-16
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2041-08-16
AI Technical Summary
Existing methods for producing foamed polyamide-based resin particles face challenges such as insufficient impregnation of carbon dioxide in the center of the pellets, leading to uneven bubble diameters and low productivity due to long impregnation times, especially when using steam as a heating medium.
A method involving the impregnation of inorganic physical foam into polyamide resin particles at a moisture content of 2.5% or more, followed by heating with hot air or an oil bath to achieve uniform independent bubbles and reduced density, even when steam is used as a heating medium.
This method ensures thorough impregnation of inorganic physical foam within polyamide resin particles, resulting in uniformly sized bubbles and lower density foamed particles with improved productivity.
Smart Images

Figure 0007624900000003 
Figure 0007624900000004 
Figure 0007624900000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing expandable polyamide-based resin particles, and further to a method for producing expanded polyamide-based resin particles by expanding the expandable polyamide-based resin particles obtained to obtain expanded particles. [Background technology]
[0002] Among general resin materials, polyamide resins are resins with high heat resistance, and are also excellent in abrasion resistance, chemical resistance, and the like. A foamed molded product obtained by foaming this polyamide resin can be made lighter while maintaining these excellent properties. For this reason, polyamide resin foamed molded products are expected to be used in automobile parts and other applications. For example, Patent Document 1 discloses polyamide resin foamed particles with excellent moldability.
[0003] Patent Document 1 describes a method in which polyamide pellets are placed in a pressure cooker at 10°C, and carbon dioxide gas at 4 MPa is blown in and absorbed for 12 hours, and then the carbon dioxide-impregnated pellets are transferred to a foaming device and air at 200°C is blown in for 20 seconds to produce foamed particles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. WO2020 / 031803 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the method of Patent Document 1 has a problem that the foaming agent, carbon dioxide gas, is difficult to sufficiently impregnate into the center of the polyamide pellets. As a result, there are problems that unfoamed parts remain in the center of the expanded beads, and the bubble diameter varies greatly. In addition, when steam is used as a heating medium, foaming itself can be difficult. Furthermore, if the foaming agent is to be reliably impregnated into the center of the polyamide pellets, a long impregnation time is required, resulting in poor productivity.
[0006] The present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to provide a method for producing expandable polyamide-based resin particles, which can sufficiently impregnate a blowing agent into the interior of polyamide-based resin particles under lower temperature conditions and / or shorter time conditions than conventional methods. [Means for solving the problem]
[0007] According to the present invention, there are provided a method for producing expandable polyamide resin particles and a method for producing expanded polyamide resin particles, which are shown below. [1] A method for producing expandable polyamide-based resin particles, comprising impregnating polyamide-based resin particles in a hygroscopic state having a water content of 2.5% by mass or more with an inorganic physical foaming agent in a gas phase. [2] The method for producing expandable polyamide-based resin particles described in item 1 above, further comprising impregnating the polyamide-based resin particles in a hygroscopic state with an inorganic physical foaming agent at a temperature higher than a temperature at which the storage modulus of the polyamide-based resin particles in a hygroscopic state changes. [3] The method for producing expandable polyamide-based resin particles according to item 2 above, wherein the temperature higher than the change point temperature of the previous storage elastic modulus is a temperature higher by 30° C. than the change point temperature and lower than 120° C. [4] The method for producing expandable polyamide-based resin particles according to any one of [1] to [3] above, wherein the aspect ratio (l / d) of the polyamide-based resin particles in a hygroscopic state is 1.1 or more and 2.5 or less. [5] The method for producing expandable polyamide-based resin particles according to any one of [1] to [4] above, wherein the melting point of the polyamide-based resin constituting the polyamide-based resin particles in a hygroscopic state is 185°C or higher and 280°C or lower. [6] A method for producing expanded polyamide-based resin particles, comprising heating and expanding the expandable polyamide-based resin particles according to any one of items 1 to 5 above to obtain expanded polyamide-based resin particles. [7] The apparent density of the foamed particles is 100 kg / m 3 More than 800kg / m 3 7. A method for producing expanded polyamide resin particles according to 6 above, which is as follows: [8] The method for producing expanded polyamide resin beads according to 6 or 7 above, wherein the expanded polyamide resin beads have a closed cell rate of 80% or more, and the ratio [Dc / D] of the average cell diameter Dc at the center of the expanded beads to the average cell diameter D of the entire expanded beads is 0.5 or more and 2.0 or less. Effect of the Invention
[0008] According to the method for producing expandable polyamide-based resin particles of the present invention, the inorganic physical foaming agent can be sufficiently impregnated into the interior of the polyamide-based resin particles at a lower temperature than conventionally used, such as room temperature, and / or in a shorter time. Furthermore, by heating the expandable polyamide-based resin particles using hot air or an oil bath, it is possible to obtain polyamide-based expanded particles having a low apparent density in which uniform closed cells are formed throughout the expanded particles. Even when steam is used as the heating medium, it is possible to obtain expanded particles having a low apparent density. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a graph plotting the relationship between the moisture content and the temperature at which the storage modulus changes in polyamide resin particles. [Diagram 2] FIG. 2 is a graph showing an example of the relationship between the storage modulus of polyamide-based resin particles measured in accordance with JIS K7095:2012 and temperature. [Diagram 3] FIG. 3 is a cross-sectional photograph of the expanded beads obtained in Example 1. [Figure 4] FIG. 4 is a cross-sectional photograph of the expanded beads obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The method for producing expandable polyamide resin particles and the method for producing expanded polyamide resin particles of the present invention will be described below in this order. In the following description, preferred numerical ranges of the present invention may be shown as appropriate. In this case, preferred ranges, more preferred ranges, and particularly preferred ranges regarding the upper and lower limits of the numerical ranges can be determined from all combinations of the upper and lower limits.
[0011] In the manufacturing method of the present invention, polyamide-based resin particles in a hygroscopic state having a water content of 2.5% by mass or more are impregnated with an inorganic physical foaming agent in a gas phase to produce expandable polyamide-based resin particles (hereinafter also referred to as expandable resin particles). That is, polyamide-based resin particles are produced using a polyamide-based resin (hereinafter also referred to as the resin particle production process), the obtained polyamide-based resin particles (hereinafter also referred to simply as resin particles) are adjusted to a moisture-absorbing state with a moisture content of 2.5% or more (hereinafter also referred to as the moisture-imparting process), and the resin particles adjusted to the moisture-imparting state are impregnated with an inorganic physical foaming agent in the gas phase to obtain expandable polyamide-based resin particles (hereinafter also referred to as the foaming agent impregnation process).
[0012] In the following description, "polyamide resin particles in a hygroscopic state with a water content of 2.5% by mass or more" may be simply referred to as "resin particles in a hygroscopic state".
[0013] If the water content of the resin particles is 2.5 mass% or more, the gas barrier properties of the polyamide-based resin are reduced, and therefore the inorganic physical foaming agent can be sufficiently impregnated into the interior of the polyamide-based resin particles in the gas phase at a lower temperature (e.g., room temperature) and / or in a shorter time than before. Therefore, by heating the expandable resin particles using a heating medium such as hot air or an oil bath, it is possible to obtain expanded particles having a high closed cell ratio, uniform closed cells formed throughout, and a low apparent density. Even when the expandable resin particles are expanded using steam as a heating medium, it is possible to obtain expanded particles having a low apparent density.
[0014] From the viewpoint of allowing the inorganic physical foaming agent to be sufficiently impregnated into the polyamide resin particles, the water content is preferably 3.0% by mass or more, more preferably 4.0% by mass or more, even more preferably 4.5% by mass or more, even more preferably 5.0% by mass or more, and particularly preferably 8.0% by mass or more. The upper limit of the water content is not particularly specified, but is generally about 20% by mass, and in order to prevent blocking during the foaming process, it is preferably 18% by mass or less, more preferably 16% by mass or less.
[0015] According to the method of the present invention, polyamide-based resin particles in a hygroscopic state having a water content of 2.5% by mass or more are used. As described later, the polyamide-based resin particles in a hygroscopic state have a tendency that the temperature at which the storage modulus changes, determined by dynamic mechanical analysis (DMA), is lower than that of polyamide-based resin particles before hygroscopic absorption. When the temperature is equal to or higher than the temperature at which the storage modulus changes, the gas barrier properties of the polyamide-based resin particles are further reduced. Therefore, the polyamide-based resin particles in a hygroscopic state can be efficiently impregnated with an inorganic physical foaming agent even under relatively low temperature conditions, such as room temperature. Similarly, the inorganic physical foaming agent can be efficiently impregnated into the resin particles even in a shorter time than before. In addition, a larger amount of the inorganic physical foaming agent can be impregnated into the resin particles.
[0016] The present invention is characterized in that the gas barrier property of polyamide resins decreases when the polyamide resins are in a hygroscopic state, and the resin particles are efficiently impregnated with a physical foaming agent. The property that the gas barrier property of polyamide resins in a hygroscopic state decreases is a property unique to polyamide resins, which is different from that of polyolefin resins and polystyrene resins that are generally used as base resins for expanded particles. As a method for obtaining expandable polyamide resin particles, a method of impregnating polyamide resin particles with an inorganic physical foaming agent in a gas phase has been known for some time. However, there was a problem that the productivity was low. The present inventors investigated the cause and inferred that the reason is that polyamide resins have significantly higher gas barrier property than polyolefin resins such as polypropylene resins, making it difficult to impregnate polyamide resin particles with an inorganic physical foaming agent. Since the polyamide resin has high gas barrier properties, even if an inorganic physical foaming agent is impregnated into the resin in the gas phase, the inorganic physical foaming agent is difficult to sufficiently impregnate into the resin, so that when the obtained expandable polyamide resin particles are heated to expand, there are cases where unexpanded portions remain in the center of the expanded particles or where the bubble diameters vary greatly. In addition, when steam is used as a heating medium, it is difficult to cause expansion.
[0017] Therefore, in the process of impregnating the resin particles with the inorganic physical foaming agent, it was thought necessary to maintain the state in which the inorganic physical foaming agent was pressed into the resin particles for a long period of time, or to impregnate the resin particles with the inorganic physical foaming agent under high temperature conditions. In response to this, the present inventors have noticed that if a polyamide resin contains a significant amount of moisture, its gas barrier properties are reduced, and have considered that this phenomenon can be utilized to promote the impregnation of the inorganic physical foaming agent. Specifically, the present inventors have considered that the impregnation of the inorganic physical foaming agent in the gas phase can be promoted by making the moisture content of the polyamide resin particles to be a specific level or higher, and have completed the manufacturing method of the present invention.
[0018] As described above, the present invention is characterized in that expandable polyamide-based resin particles are obtained by impregnating resin particles in a hygroscopic state having a water content of 2.5% by mass or more with an inorganic physical foaming agent in a gas phase. Specifically, expandable polyamide-based resin particles can be obtained by a method including a resin particle production step of preparing polyamide-based resin particles, a moisture-containing step of bringing the polyamide-based resin particles into a moisture-absorbing state, and a foaming agent impregnation step of impregnating the moisture-absorbing polyamide-based resin particles with an inorganic physical foaming agent in a gas phase.Furthermore, expanded polyamide-based resin particles can be obtained by a method including a foaming step of heating the expandable resin particles. The resin particle production step, the water-containing step, the foaming agent impregnation step, and the foaming step will be described below in this order.
[0019] (Resin particle manufacturing process) In the resin particle production process, polyamide resin particles are produced by processing a polyamide resin. Specifically, the following methods can be mentioned as representative methods for producing polyamide-based resin particles. First, polyamide-based resin and additives such as a bubble regulator, an end-capping agent, and a colorant, which are blended as necessary, are melt-kneaded in an extruder to produce a melt-kneaded product. Next, the melt-kneaded product is extruded from a small hole in a die attached to the tip of the extruder, cut to a predetermined size, and granulated to produce polyamide-based resin particles. In addition, examples of a method for cutting the extruded melt-kneaded product include a strand cut method in which the extruded strand-shaped melt-kneaded product is cut to a predetermined weight with a pelletizer, a hot cut method in which the melt-kneaded product is extruded into a gas phase and cut immediately thereafter, and an underwater cut method (UWC method) in which the melt-kneaded product is extruded into water and cut immediately thereafter. However, commercially available polyamide-based resin particles can also be used.
[0020] The polyamide-based resin used in the production of the polyamide-based resin particles may be a single resin or a mixed resin in which two or more types are combined. The polyamide resin may be polyamide or a polyamide copolymer, with the polyamide copolymer being preferred. Examples of such polyamides include poly(6-aminohexanoic acid), also known as poly(caprolactam) (polycaproamide, nylon 6), poly(laurolactam) (nylon 12), poly(hexamethylene adipamide) (nylon 66), poly(7-aminoheptanoic acid) (nylon 7), poly(8-aminooctanoic acid) (nylon 8), poly(9-aminononanoic acid) (nylon 9), poly(10-aminodecanoic acid) (nylon 10), poly(11-aminounsodium tert-butyl ether) (nylon 11), poly(12-aminohexanoic acid) (nylon 12), poly(1 ... Examples of homopolymers include poly(hexamethylene sebacamide) (nylon 11), poly(hexamethylene sebacamide) (nylon 610), poly(decamethylene sebacamide) (nylon 1010), poly(hexamethylene azelamide) (nylon 69), poly(tetramethylene adipamide) (nylon 46), poly(tetramethylene sebacamide) (nylon 410), poly(pentamethylene adipamide) (nylon 56), and poly(pentamethylene sebacamide) (nylon 510). The polyamide copolymer means a copolymer having two or more kinds of repeating units, at least a part of each repeating unit having an amide bond. Examples of the polyamide copolymer include polycaproamide / polyhexamethylene adipamide copolymer (nylon 6 / 66), caprolactam / hexamethylenediaminoadipic acid / lauryllactam (nylon 6 / 66 / 12), and caprolactam / lauryllactam copolymer (nylon 6 / 12). The polyamide resin may be one of these polyamides and polyamide copolymers, or a combination of two or more of them. Among the above polyamide resins, from the viewpoint of excellent foaming properties, a polyamide resin comprising one or a combination of two or more selected from nylon 6, nylon 66, nylon 6 / 66 / 12, and nylon 6 / 66 is preferred, and nylon 6 / 66 is more preferred. From the same viewpoint, the polyamide copolymer is preferably a random copolymer in which different types of amides are randomly repeated.
[0021] From the viewpoint of improving the heat resistance of the finally obtained expanded beads and expanded bead molded articles, the melting point of the polyamide resin is preferably 180° C. or higher, and more preferably 185° C. or higher. On the other hand, from the viewpoint of reducing the load on the device when the expandable polyamide resin particles impregnated with the inorganic physical foaming agent are heated by a heating medium, the melting point is preferably 280° C. or lower, more preferably 260° C. or lower, and even more preferably 240° C. or lower.
[0022] The melting point of the polyamide resin refers to the melting point of the polyamide resin when the expandable resin particles are made of a single polyamide resin. When the expandable resin particles are made of a mixture of two or more polyamide resins, the melting point of the polyamide resin refers to the melting point of the mixture kneaded in advance in an extruder or the like.
[0023] The melting point of the polyamide resin is measured in accordance with JIS K7121-1987. Specifically, by heat flux differential scanning calorimetry, the resin is heated and melted (first heating) from 30°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min, then held at that temperature for 10 minutes, cooled to 30°C at a cooling rate of 10°C / min, and then heated and melted again at a heating rate of 10°C / min to a temperature 30°C higher than the end of the melting peak. The melting point of the polyamide resin can be determined as the temperature at the top of the melting peak of the second DSC curve (melting peak temperature). When the DSC curve has multiple melting peaks, the melting peak temperature of the melting peak with the largest area is used as the melting point of the polyamide resin. The polyamide resin to be measured has a water content of 1000 mass ppm or less. As a measuring device, for example, a high-sensitivity differential scanning calorimeter "EXSTAR DSC7020" (manufactured by SII Nanotechnology Co., Ltd.) can be used.
[0024] The flexural modulus of the polyamide resin is preferably 1000 MPa or more, more preferably 1050 MPa or more. If the flexural modulus of the polyamide resin is within this range, the high flexural modulus makes it difficult to shrink even when exposed to room temperature after foaming, and it is easier to obtain expanded particles with a small apparent density, which is preferable. The upper limit of the flexural modulus of the polyamide resin is about 3000 MPa. The flexural modulus of the amide elastomer is about 600 MPa or less.
[0025] The flexural modulus of the polyamide-based resin is measured in accordance with JIS K7171: 2016. The polyamide-based resin to be used for the measurement has a water content of 1000 ppm by mass or less.
[0026] The density of the polyamide resin is 1.05 g / cm 3 It is preferable that the content is 1.1 g / cm or more. 3 It is more preferable that the density of the amide elastomer is 1.05 g / cm or more. 3 The density of the polyamide resin can be determined based on the method described in ISO1183-3.
[0027] The polyamide resin particles may contain other polymers such as thermoplastic resins other than polyamide resins and thermoplastic elastomers, within the scope of not impairing the object and effect of the present invention. Examples of other thermoplastic resins include polyethylene resins, polypropylene resins, polystyrene resins, vinyl acetate resins, thermoplastic polyester resins, acrylic acid ester resins, methacrylic acid ester resins, polyphenylene sulfide resins, etc. Examples of thermoplastic elastomers include styrene thermoplastic elastomers, olefin thermoplastic elastomers, amide thermoplastic elastomers, etc. The content of the other polymers is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the polyamide resin particles, and it is particularly preferable that the polymers do not contain other polymers other than polyamide resins.
[0028] In addition to the polyamide resin, the polyamide resin particles may be appropriately blended with various additives such as commonly used bubble regulators, end-capping agents, antistatic agents, conductive agents, weathering agents, lubricants, antioxidants, ultraviolet absorbers, flame retardants, metal deactivators, colorants (pigments, dyes, etc.), crystal nucleating agents, and fillers, as necessary. Examples of bubble regulators include inorganic bubble regulators such as talc, sodium chloride, calcium carbonate, silica, titanium oxide, gypsum, zeolite, borax, aluminum hydroxide, alum, and carbon, and organic bubble regulators such as phosphoric acid compounds, amine compounds, and polytetrafluoroethylene (PTFE). The amount of these various additives to be added varies depending on the purpose of use of the resulting molded product, but is preferably 25 parts by mass or less per 100 parts by mass of the polyamide resin particles. More preferably, it is 15 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less.
[0029] The polyamide-based resin particles may be resin particles having a single layer structure, or may be multi-layer resin particles having a multi-layer structure. The multi-layer structure refers to a structure having a core layer and a coating layer covering the core layer, the core layer and the coating layer being composed of polyamide-based resins having different properties. The multi-layer resin particles are expanded in a foaming process described later to become expanded particles having an expanded core layer in a foamed state and a coating layer covering the expanded core layer. When the polyamide-based resin particles are multi-layer resin particles, from the viewpoint of improving the fusion between the expanded particles while maintaining heat resistance, the melting point (Tms) of the polyamide-based resin constituting the coating layer is preferably lower than the melting point (Tmc) of the polyamide-based resin constituting the core layer, and more preferably 20°C or more lower than the melting point (Tmc). From the viewpoint of suppressing the peeling between the coating layer and the core layer, [(Tmc)-(Tms)] is preferably 40°C or less. In addition, from the viewpoint of improving the fusion, the coating layer is preferably in a non-foamed state. The non-foamed state includes a state in which bubbles have disappeared after foaming, and bubbles may be present in part in the layer.
[0030] The ratio of the length l of the polyamide resin particle to the diameter d of the resin particle (aspect ratio l / d) is preferably adjusted to 1.1 or more, more preferably 1.2 or more. If the aspect ratio of the resin particle (aspect ratio l / d) is within this range, the impregnation efficiency of the inorganic physical foaming agent in the gas phase can be further improved. In addition, since the foamed particles can be efficiently molded in the mold, the upper limit of the ratio is 2.5, more preferably 2.0, and even more preferably 1.5. The aspect ratio l / d of a polyamide resin particle is determined by measuring the maximum length l and the maximum cross-sectional diameter d of a cross-section of a resin particle in a direction perpendicular to the longitudinal direction of the maximum length for 50 randomly selected resin particles using a vernier caliper or the like, calculating the ratio l / d, and then taking the arithmetic average of these values.
[0031] (hydrous process) In the production method of the present invention, since polyamide-based resin particles in a moisture-absorbed state with a moisture content of 2.5% by mass or more are used, a moisture-absorbed step is appropriately performed to adjust the polyamide-based resin particles to a moisture-absorbed state with a moisture content of 2.5% by mass or more. The moisture-absorbed step may be performed before the polyamide-based resin particles are placed in a pressure-resistant vessel for impregnating with an inorganic physical foaming agent, or may be performed in the pressure-resistant vessel after the polyamide-based resin particles are placed in the pressure-resistant vessel. However, in order to further improve productivity, it is preferable to charge polyamide resin particles, the moisture content of which has been adjusted in advance to 2.5% by mass or more, into a pressure vessel, and then to pressurize the inorganic physical foaming agent into the vessel. When the resin particles are subjected to a moisture impregnation treatment after being placed in a pressure-resistant vessel, the moisture content of the resin particles is measured by removing the hygroscopic resin particles that have been subjected to a moisture impregnation treatment under the same conditions from the pressure-resistant vessel.
[0032] If an inorganic physical foaming agent is impregnated into polyamide-based resin particles in a dry state having a moisture content of less than 2.5% by mass, the inorganic physical foaming agent may not be sufficiently impregnated into the interior of the resin particles in the foaming agent impregnation step described below, making it difficult to foam the particles, or unfoamed areas may remain inside the foamed particles or there may be significant unevenness in the distribution of air bubbles.
[0033] In addition, when impregnating resin particles made of polyolefin resin such as polypropylene resin with inorganic physical foaming agent in gas phase, dry resin particles with moisture content of 0.1% or less are usually put into a pressure-resistant container and impregnated with foaming agent. In addition, in the conventional process of impregnating polyamide resin particles with inorganic physical foaming agent in gas phase, the polyamide resin particles have not been adjusted to a moisture-absorbed state with moisture content of 2.5% by mass or more. In contrast, in the manufacturing method of the present invention, expandable polyamide resin particles are manufactured by impregnating polyamide resin particles with moisture content of 2.5% by mass or more with inorganic physical foaming agent.
[0034] The moisture-imparting step may be any method that can adjust the moisture content of the polyamide-based resin particles to a desired range. For example, there may be mentioned a first moisture-imparting method in which the polyamide-based resin particles are left in a standard state (e.g., 1 atm, temperature 23°C, humidity 50%) for 12 hours or more, preferably 24 hours or more, a second moisture-imparting method in which the polyamide-based resin particles are left in a high-temperature and high-humidity state (e.g., temperature 40°C, humidity 80%) for 3 hours or more, preferably 5 hours or more, a third moisture-imparting method in which the polyamide-based resin particles are immersed in water and left to stand for about 10 seconds to 4 hours, a fourth moisture-imparting method in which the polyamide-based resin particles are placed in a bag or container together with water and manually or mechanically stirred or mixed, or a fifth moisture-imparting method in which water is applied to the polyamide-based resin particles by a shower, a sprayer, or the like. These moisture-imparting steps may also be carried out in combination. Polyolefin resins and amide elastomers have low moisture absorption properties, and therefore, these moisture-containing methods generally cannot bring them into a moisture-absorbed state with a moisture content of 2.5% by mass or more.
[0035] These water-imparting methods can adjust the water content of the polyamide resin particles as a whole to a desired range while suppressing the variation in water content among the resin particles, which allows the foaming agent to be impregnated sufficiently into the resin particles even in a short time and / or at a low temperature in the foaming agent impregnation step described below. The first moisture-containing method is suitable for obtaining polyamide-based resin particles having a moisture content of about 2.5% to 4% by mass. The second, third, and fourth moisture-containing methods are suitable for obtaining polyamide-based resin particles having a moisture content of 4% or more by mass, or 4.5% or more by mass. From the viewpoint of obtaining resin particles having a uniform moisture content in a shorter time, the second or third moisture-containing method is preferred.
[0036] In the first moisture-containing method and the second moisture-containing method, leaving the polyamide-based resin particles under standard conditions and high-temperature, high-humidity conditions means exposing the resin particles directly or indirectly to the respective conditions, and includes, for example, placing the polyamide-based resin particles in an open container, bag, tray, etc. in a room maintained under specified conditions, and placing the polyamide-based resin particles in a closed but non-sealed container or bag, etc.
[0037] In the present invention, the moisture content of the polyamide resin particles can be measured using a halogen moisture meter. A specific example of the measuring device is a halogen moisture meter (HX204) manufactured by METTLER TOLEDO, which measures the moisture content based on halogen lamp heating. Specifically, the moisture content of polyamide resin particles can be measured by the following method. First, about 2.0 g of polyamide resin particles, which have been wiped to remove moisture from the surface of the resin particles, are weighed and used as a measurement sample. Next, the measurement sample is heated to a temperature of 100°C using a halogen moisture meter, and maintained at 100°C for 60 seconds until no weight change occurs, and then further heated to 160°C and maintained at 160°C for 90 seconds until no weight change occurs, thereby vaporizing the moisture inside the measurement sample. The weight loss due to heating at this time is divided by the weight of the resin particles before heating and converted into a percentage to calculate the moisture content (%). The moisture content of the polyamide film described later can be determined by the same method as that of the polyamide resin particles, except that the weight of the measurement sample is about 0.5 g.
[0038] In the polyamide-based resin particles in the hygroscopic state, the ratio of the length l of the resin particles to the diameter d of the resin particles (aspect ratio l / d) is preferably 1.1 or more, more preferably 1.2 or more. When the aspect ratio l / d of the polyamide-based resin particles in the hygroscopic state is within this range, the impregnation efficiency of the inorganic physical foaming agent in the gas phase can be further improved. In addition, from the viewpoint of efficiently filling the obtained expanded particles into a molding die, the upper limit of the aspect ratio l / d is 2.5, more preferably 2.0, and even more preferably 1.5. The aspect ratio l / d of polyamide resin particles in a dry state hardly changes even when the particles become hygroscopic.
[0039] The aspect ratio l / d of the polyamide resin particles in a hygroscopic state is determined by measuring the maximum length l and the maximum cross-sectional diameter d of the cross section of the resin particle in a direction perpendicular to the longitudinal direction of the maximum length for 50 randomly selected resin particles after the hydration step using a vernier caliper or the like, calculating the ratio l / d, and then taking the arithmetic average of these ratios.
[0040] (Foaming agent impregnation process) Next, the foaming agent impregnation step will be described. In the foaming agent impregnation step, polyamide-based resin particles in a hygroscopic state with a moisture content of 2.5% by mass or more are impregnated with an inorganic physical foaming agent in the gas phase. The polyamide-based resin particles in a hygroscopic state with a moisture content of 2.5% by mass or more used in the foaming agent impregnation step are obtained by the resin particle production step described above and a moisture impregnation step that is carried out as necessary.
[0041] In the foaming agent impregnation step, for example, resin particles in a hygroscopic state with a water content of 2.5% by mass or more are placed in a pressure vessel, and an inorganic physical foaming agent is pressurized into the polyamide resin particles to impregnate the inorganic physical foaming agent in the gas phase, thereby obtaining expandable polyamide resin particles.
[0042] The foaming agent used is an inorganic physical foaming agent, such as carbon dioxide, nitrogen, helium, argon, or air. Among the inorganic physical foaming agents, carbon dioxide or air is preferred, and carbon dioxide is more preferred, from the viewpoints of having less impact on the environment, being non-flammable, and being excellent in safety.
[0043] When the above-mentioned resin particles in a moisture-absorbing state are impregnated with an inorganic physical foaming agent in a gas phase, the impregnation efficiency of the inorganic physical foaming agent is strongly affected by the impregnation temperature and the moisture content of the resin particles.
[0044] Next, the temperature in the foaming agent impregnation step will be described. In the foaming agent impregnation step, when the inorganic physical foaming agent is impregnated into the polyamide resin particles in a hygroscopic state, it is preferable to carry out the impregnation at a temperature higher than the change point temperature of the storage modulus of the polyamide resin particles in a hygroscopic state (hereinafter, simply referred to as the change point temperature of the storage modulus or the change point temperature). That is, in the foaming agent impregnation step, it is preferable to set the temperature in the pressure-resistant container in the foaming agent impregnation step higher than the change point temperature of the storage modulus of the polyamide resin particles in a hygroscopic state, using the change point temperature as an index. In this way, the impregnation efficiency of the inorganic physical foaming agent can be further improved.
[0045] Next, the use of the change point temperature of the storage elastic modulus as an index will be described. The present inventors have found that the temperature at which the storage modulus changes, determined by dynamic viscoelasticity measurement of a water-absorbed polyamide resin, can be used as an index of the set temperature in the foaming agent impregnation step. As shown in Fig. 1, the higher the water content of the polyamide resin particles, the lower the temperature at which the storage modulus changes, and at temperatures above the temperature at which the storage modulus changes, the gas barrier properties of the polyamide resin constituting the resin particles are further reduced. Therefore, the inventors have found that if the temperature is higher than the temperature at which the storage modulus changes of the hygroscopic resin particles, the gas barrier properties of the polyamide resin are further reduced, and therefore the inorganic physical foaming agent can be more efficiently impregnated into the resin particles. As described later, Fig. 1 is a graph plotting the relationship between the moisture content of a polyamide film made from polyamide resin particles and the temperature at which the storage modulus changes, with the moisture content on the horizontal axis and the temperature at which the storage modulus changes on the vertical axis. Fig. 1 shows that, in the polyamide resin particles, the temperature at which the storage modulus changes decreases as the moisture content (%) increases.
[0046] In addition, by measuring dynamic mechanical properties (DMA), in addition to the storage modulus, the loss modulus and the loss tangent can be obtained. Among these physical property values, the change point temperature of the storage modulus is the lowest temperature at which the molecular motion of the resin material being measured starts to change (the elastic modulus changes), and it is considered that at or above this temperature, the inorganic physical foaming agent can be sufficiently impregnated into the interior of the polyamide resin particles at a lower temperature (for example, room temperature) and / or in a shorter time than before. Therefore, in the present invention, it is considered that the change point temperature of the storage modulus can be used as an index of the lower limit temperature at which the inorganic physical foaming agent can be more efficiently impregnated into the polyamide resin particles.
[0047] In the present invention, the storage modulus inflection point temperature of the polyamide resin particles means the storage modulus inflection point temperature (glass transition temperature from the curve of storage modulus versus temperature) obtained by dynamic viscoelastic measurement (DMA) in accordance with JIS K7095:2012.
[0048] The storage modulus change temperature of the polyamide-based resin particles is a value that can be calculated by using a relational equation between the moisture content and the storage modulus change temperature obtained by plotting the relationship between the moisture content and the storage modulus change temperature in a polyamide film made from a plurality of polyamide-based resin particles composed of the same type of polyamide-based resin as the polyamide-based resin particles for which the storage modulus change temperature is to be determined, and then using the relational equation to obtain the moisture content of the polyamide resin particles for which the storage modulus change temperature is to be determined.
[0049] Specifically, polyamide resin particles are compressed by a heat press heated to 210°C to prepare a polyamide film of 100mm length x 100mm width x 0.4mm thickness. From this polyamide film, a film-shaped sample A (40mm length x 50mm width x 0.4mm thickness) for determining the moisture content of the polyamide film and a film-shaped sample B (40mm length x 5mm width x 0.4mm thickness) for measuring the change point temperature of the storage modulus of the polyamide film are cut out. The moisture content of the film-shaped sample A is measured in advance by the above-mentioned method. The film-shaped sample B is fixed with a jig, and the temperature is raised from -80°C to 130°C at a heating rate of 2°C / min in a tensile mode with a constant frequency (1Hz) to measure the storage modulus. Then, as shown in FIG. 2, the measurement results are plotted to create a graph with the vertical axis representing the storage modulus and the horizontal axis representing the temperature. 2 is an example of a graph showing the relationship between the storage modulus and temperature of polyamide-based resin particles measured in accordance with JIS K7095: 2012. As the DMA measuring device, for example, DMA7100 manufactured by Hitachi High-Tech Science Corporation can be used.
[0050] In the graph of Figure 2, the temperature indicated by the perpendicular line drawn downward from the intersection B between the line L1, which is an extension to the high temperature side of the straight line portion before the initial rapid drop in the storage modulus, and the line L2, which is an extension to the low temperature side of the straight line portion of the midpoint after the initial rapid drop in the storage modulus, is taken as the storage modulus change temperature. If multiple storage modulus change temperatures appear, the lowest change temperature is used. The above measurement is carried out on 10 polyamide films that have been adjusted to the same moisture content in advance, and the arithmetic average value is taken as the storage modulus change temperature of the polyamide film at that moisture content.
[0051] The above measurement is carried out using a polyamide film made from a plurality of polyamide resin particles having different moisture contents, and the moisture content of the polyamide film is plotted on the horizontal axis and the storage modulus on the vertical axis to obtain a relational expression between the moisture content and the change point of the storage modulus. An example of this plot is shown in Figure 1. Then, the change point temperature of the storage modulus is calculated using the relational expression from the moisture content value of the polyamide resin particles for which the change point temperature of the storage modulus is to be obtained.
[0052] Next, the relationship between the water content and the impregnation efficiency of the inorganic physical foaming agent will be described. The higher the moisture content of the polyamide-based resin particles, the higher the impregnation efficiency of the inorganic physical foaming agent can be. Also, the higher the moisture content of the polyamide-based resin particles, the lower the temperature at which the storage modulus changes, so that the inorganic physical foaming agent can be efficiently impregnated into the polyamide-based resin particles even at a lower temperature, or the time required for impregnation with the inorganic physical foaming agent can be shortened by maintaining the temperature. From this point of view, the moisture content of the polyamide-based resin particles in a hygroscopic state is preferably 3.0% by mass or more, more preferably 4.0% by mass or more, even more preferably 4.5% by mass or more, even more preferably 5.0% by mass or more, and particularly preferably 8.0% by mass or more.
[0053] On the other hand, the upper limit of the moisture content of the polyamide resin particles is not particularly specified. However, as shown in Fig. 1, as the moisture content increases, the degree of decrease in the temperature at the change point of the storage modulus decreases and an equilibrium state is reached, so the upper limit of the moisture content is about 20% by mass. From the viewpoint of preventing blocking in the foaming process described later, the upper limit of the moisture content is preferably 18% by mass or less, and more preferably 16% by mass or less.
[0054] The reason why the higher the water content of the polyamide-based resin particles, the lower the temperature at which the storage modulus changes is believed to be that the presence of water molecules weakens the intermolecular interactions due to hydrogen bonds between the polyamide-based resin molecules, thereby changing the molecular motion of the polyamide-based resin.
[0055] Next, the relationship between the impregnation temperature and the impregnation time in the foaming agent impregnation step will be described. As described above, in the foaming agent impregnation step, it is preferable to adjust the temperature inside the pressure vessel in the foaming agent impregnation step to be higher than the change point temperature of the storage modulus of the polyamide resin particles in a moisture-absorbed state. Furthermore, in order to more efficiently impregnate the resin particles with the inorganic physical foaming agent, it is preferable to adjust the temperature in the pressure vessel in the foaming agent impregnation step to be higher than the temperature at which the storage modulus of the polyamide resin particles in a hygroscopic state changes during more than 50% of the total implementation time of the foaming agent impregnation step. Here, the total implementation time of the foaming agent impregnation step refers to the time from the start of the foaming agent impregnation step to the removal of the expandable polyamide resin particles impregnated with the foaming agent. Furthermore, the start of the foaming agent impregnation step refers to the first time when the resin particles put into the pressure vessel have a moisture content of 2.5% by mass or more and the inorganic physical foaming agent is pressed into the pressure vessel. Either the time when the moisture content of the resin particles reaches 2.5% by mass or more or the time when the inorganic physical foaming agent starts to be pressed into the pressure vessel may occur first. Specifically, for example, polyamide-based resin particles with a moisture content of 2.5% by mass or more may be put into the pressure vessel and the inorganic physical foaming agent may be pressed into the pressure vessel, or, for example, dry polyamide-based resin particles with a moisture content of less than 2.5% by mass may be put into the pressure vessel and the inorganic physical foaming agent may be pressed into the pressure vessel, and then, at any timing, a treatment may be performed to increase the moisture content of the polyamide-based resin particles in the pressure vessel to 2.5% by mass or more. The period of time that exceeds 50% of the total implementation time of the foaming agent impregnation step may be a continuous period of time within the total implementation time, or may be the sum of intermittent periods of time.
[0056] From the viewpoint of more sufficient impregnation with the blowing agent, the time during which the temperature inside the pressure vessel is maintained higher than the change point temperature of the storage modulus of the polyamide-based resin particles in a hygroscopic state in the blowing agent impregnation step is preferably 70% or more of the total implementation time of the blowing agent impregnation step, more preferably 80% or more, particularly preferably 90% or more, and most preferably substantially 100%.
[0057] The temperature inside the pressure vessel during the time exceeding 50% of the total implementation time of the foaming agent impregnation process may be adjusted to a constant temperature or may be varied. During the foaming agent impregnation process, the moisture content of the polyamide resin particles changes over time, and the temperature at which the storage modulus changes may change over time. Therefore, the temperature at which the storage modulus of the polyamide resin particles changes, which is an index for determining the temperature at which the temperature inside the pressure vessel should be set, refers to the temperature at which the storage modulus changes, which is measured by taking out the polyamide resin particles having the moisture content at that time from the pressure vessel.
[0058] As described above, the storage modulus change temperature of the polyamide-based resin particles in a hygroscopic state is lower than that of the polyamide-based resin particles in a dry state. Therefore, the inorganic physical foaming agent can be impregnated at a lower temperature and / or in a shorter time than when the polyamide-based resin particles in a dry state are used. As a result, the load on the equipment such as the pressure-resistant container can be reduced, and the productivity can be improved. In addition, discoloration due to deterioration of the resin can be suppressed.
[0059] The temperature in the pressure vessel in the foaming agent impregnation step is not particularly limited, but as described above, it is preferable to impregnate the inorganic physical foaming agent into the polyamide resin particles in a hygroscopic state at a temperature higher than the change point temperature of the storage modulus of the polyamide resin particles in a hygroscopic state.In this case, it is more preferable to impregnate the inorganic physical foaming agent into the resin particles at a temperature higher than the change point temperature at the start of the foaming agent impregnation step. That is, during the foaming agent impregnation step, the moisture content of the resin particles in a hygroscopic state in the pressure vessel gradually decreases, and the temperature at which the storage modulus changes tends to rise compared to the start of the foaming agent impregnation step. On the other hand, by setting the impregnation temperature of the inorganic physical foaming agent to a temperature higher than the change temperature at the start of the foaming agent impregnation step, even if the change temperature rises during the impregnation with the inorganic physical foaming agent, the inorganic physical foaming agent can be sufficiently impregnated into the polyamide resin particles without any particular problem. Furthermore, the impregnation efficiency of the inorganic physical foaming agent can be further improved, the impregnation time of the inorganic physical foaming agent can be significantly shortened, and a larger amount of the inorganic physical foaming agent can be impregnated.
[0060] Specifically, the impregnation temperature of the inorganic physical foaming agent is more preferably at least 10° C. higher than the change point temperature at the start of the foaming agent impregnation step, even more preferably at least 25° C. higher, even more preferably at least 30° C. higher, and particularly preferably at least 45° C. higher. On the other hand, from the viewpoint of reducing the load on an apparatus such as a pressure-resistant vessel, the temperature of the foaming agent impregnation step is preferably at most 100° C. higher than the change point temperature at the start of the foaming agent impregnation step, more preferably at most 80° C. higher, even more preferably at most 75° C. higher, and particularly preferably at most 70° C. higher.
[0061] In the present invention, it is most preferable to impregnate the inorganic physical foaming agent at a temperature in the pressure vessel in the foaming agent impregnation step that is 30° C. or higher than the change-point temperature at the start of the foaming agent impregnation step for more than 50% of the total implementation time of the foaming agent impregnation step. For example, if the change-point temperature of the storage modulus of the polyamide resin particles in a hygroscopic state at the start of the foaming agent impregnation step is −10° C., it is preferable to set the temperature in the pressure vessel in the foaming agent impregnation step to 20° C. or higher and maintain it at 20° C. or higher for more than 50% of the total implementation time of the foaming agent impregnation step.
[0062] In the present invention, it is more preferable to adjust the temperature in the pressure vessel to be higher than the temperature at which the storage modulus of the polyamide-based resin particles in a hygroscopic state changes in the initial stage of the foaming agent impregnation process. Here, the initial stage of the foaming agent impregnation process refers to a time point from the start of the foaming agent impregnation process until 5% of the total implementation time of the foaming agent impregnation process has elapsed, preferably until 3% has elapsed, more preferably until 1% has elapsed, and most preferably at the start of the foaming agent impregnation process.
[0063] It is further preferable to start impregnating the inorganic physical foaming agent at a temperature 30° C. or more higher than the change-point temperature at the start of the foaming agent impregnation step from the initial stage of the foaming agent impregnation step, and to continuously maintain the temperature 30° C. or more higher than the change-point temperature until the final stage of the foaming agent impregnation step. Here, the final stage of the foaming agent impregnation step refers to the time from 95% to 100% of the total implementation time of the foaming agent impregnation step from the start, preferably the time from 97% to 100%, and more preferably the time from 99% to 100%.
[0064] The upper limit of the temperature in the foaming agent impregnation step is not particularly specified, and can be determined in consideration of the relationship with other conditions such as the moisture content of the resin particles, the impregnation time of the inorganic physical foaming agent, etc. However, from the viewpoint of reducing the load on the apparatus and suppressing discoloration and the like due to deterioration of the resin, the impregnation temperature of the inorganic physical foaming agent in the foaming agent impregnation step is preferably 150°C or less, more preferably 120°C or less, even more preferably 100°C or less, even more preferably 80°C or less, particularly preferably 50°C or less, and most preferably 30°C or less.
[0065] Next, the pressure in the pressure vessel in the foaming agent impregnation step will be described. The pressure inside the pressure vessel into which the hygroscopic polyamide resin particles are charged increases as the inorganic physical foaming agent is pressed in. This allows the inorganic physical foaming agent to be impregnated into the hygroscopic resin particles. The relationship between the injection of the inorganic physical foaming agent and the adjustment of the temperature inside the pressure vessel is not particularly limited, and the injection of the foaming agent and the temperature adjustment may be started simultaneously, or one of them may be started first, or the temperature adjustment may be started first and the injection of the foaming agent may be started after the temperature reaches a predetermined temperature. The rate at which the pressure of the foaming agent injected into the pressure vessel increases is not particularly limited.
[0066] The pressure in the pressure vessel increases by injecting the inorganic physical foaming agent. The pressure in the pressure vessel is not particularly limited, but is preferably in the range of 2.0 MPa (G) to 6.0 MPa (G), and more preferably in the range of 3.0 MPa (G) to 5.0 MPa (G). In addition, the pressure in the pressure vessel is preferably kept constant throughout the entire duration of the foaming agent impregnation step. However, the pressure in the pressure vessel may be varied.
[0067] The foaming agent impregnation step provides expandable polyamide-based resin particles for producing expanded beads, i.e., "expandable polyamide-based resin particles that can be expanded by heating, which are obtained by impregnating polyamide-based resin particles in a hygroscopic state having a water content of 2.5% or more with an inorganic physical foaming agent in a gas phase."
[0068] (Foaming process) The foaming step is a step of heating and foaming the expandable polyamide resin particles obtained in the foaming agent impregnation step. The polyamide resin expandable resin particles impregnated with the inorganic physical foaming agent are heated and foamed to obtain polyamide resin expanded particles. The foaming step is preferably carried out promptly after the foaming agent impregnation step. The method of heating the expandable resin particles is not particularly limited. For example, a method of heating by supplying high-temperature air (hot air foaming), a method of heating by immersing in high-temperature oil (oil bath foaming), a method of heating by supplying steam (water vapor) (steam foaming), etc. can be mentioned. By heating the expandable resin particles using hot air or an oil bath, it is possible to obtain polyamide-based resin expanded particles having uniform closed cells formed throughout and having a low apparent density. From the viewpoint of more easily obtaining such expanded particles, the temperature of the hot air supplied in the hot air foaming is preferably 180°C or more and 300°C or less, more preferably 200°C or more and 280°C or less, and even more preferably 220°C or more and 250°C or less. From the same viewpoint, the temperature of the hot air supplied in the hot air foaming is preferably 10°C higher or more and 100°C higher or less than the melting point of the polyamide-based resin constituting the polyamide-based resin particles, and more preferably 20°C higher or more and 80°C higher or less than the melting point of the polyamide-based resin. In addition, in the past, when expanding resin particles were supplied with steam as a heating medium to produce expanded particles, the expansion itself was sometimes difficult. However, according to the present invention, even when steam is used as a heating medium, expanded particles having a low apparent density can be produced. From the viewpoint of more easily obtaining such expanded particles, the temperature of the steam supplied in the steam expansion is preferably 100°C or higher and 180°C or lower, more preferably 120°C or higher and 150°C or lower.
[0069] The foaming step may be performed under pressure. The pressure is not particularly limited, but may be adjusted to within a range of, for example, 0.03 MPa to 0.4 MPa. The heating time may be within a range of, for example, 5 seconds to 120 seconds.
[0070] (Polyamide resin foam particles) Next, the apparent density and closed cell ratio of the expanded polyamide resin beads obtained by the present invention will be described in this order. By carrying out the above-mentioned foaming agent impregnation step and foaming step, expanded beads having a low apparent density can be produced. According to the production method of the present invention, for example, expanded beads having an apparent density of 800 kg / m 3 It is possible to obtain expanded beads having an apparent density of 750 kg / m or less, and more preferably, the apparent density is 750 kg / m or less. 3 Less than or equal to 600 kg / m 3 Less than 600 kg / m, more preferably 600 kg / m 3 The apparent density of the expanded polyamide resin beads obtained by the foaming agent impregnation step and the foaming step can be adjusted to the following values. This allows for a lightweight polyamide resin expanded bead molding to be obtained. The lower limit of the apparent density of the expanded polyamide resin beads obtained by the foaming agent impregnation step and the foaming step is not particularly limited, but is generally 100 kg / m 3 It is. To further reduce the weight, expanded beads having an apparent density lower than the above-mentioned range of apparent density (second-stage expanded beads) can be produced by applying an internal pressure to the expanded beads and heating them.
[0071] The apparent density of the expanded polyamide resin beads is measured by the following method. Prepare a measuring cylinder containing water at a temperature of 23°C. Add approximately 500 cm 3 The weight Wp of the foamed particles is measured and submerged using a wire net. Taking into account the volume of the wire net, the volume Vp [cm 3 ] was measured, and the weight Wp [g] of the foam particles was divided by the volume Vp (Wp / Vp) and expressed in units of [kg / m 3 The expanded beads to be used for the measurement are cured in an oven at 80°C for 12 hours, and then slowly cooled to a dry state.
[0072] The closed cell ratio of the expanded polyamide resin beads obtained by the present invention is preferably 70% or more, more preferably 80% or more. When the closed cell ratio satisfies this range, the moldability of the expanded beads becomes better, and the expanded bead molding obtained by molding the expanded beads in a mold has better surface properties and fusion properties. The closed cell ratio can be determined using an air comparison type specific gravity meter based on procedure C described in ASTM-D2856-70. The expanded beads to be used for the measurement are cured in an oven at 80° C. for 12 hours and then slowly cooled to a dry state.
[0073] The average cell diameter D of the expanded polyamide resin beads obtained by the present invention is preferably 50 μm or more and 300 μm or less, more preferably 80 μm or more and 250 μm or less, and even more preferably 100 μm or more and 200 μm or less. When the average cell diameter of the expanded beads is within this range, the moldability is improved. The average cell diameter D can be determined by the following method. First, the expanded bead is cut into approximately two equal halves passing through the center of the expanded bead, and one of the cut surfaces is photographed with a scanning electron microscope so that the entire surface of the cut surface is captured. Next, in the obtained cross-sectional photograph, lines are drawn at 45° intervals in eight directions from near the center of the cut surface of the expanded bead, and the number of bubbles intersecting the lines is counted. The total length of the lines is divided by the number of bubbles counted, and the resulting value is defined as the cell diameter of the expanded beads. This operation is performed in the same manner for 10 expanded beads, and the arithmetic mean value of the cell diameters of each expanded bead is defined as the average cell diameter D of the expanded beads.
[0074] The ratio (Dc / D) of the average cell diameter Dc at the center of the expanded beads to the average cell diameter D of the expanded beads is preferably 0.5 to 2.0, more preferably 0.8 to 1.8, and even more preferably 0.9 to 1.5. The ratio (Dc / D) within this range means that a uniform cell structure is formed throughout the expanded beads. The average cell diameter Dc at the center of the expanded beads can be obtained by the following method. First, the expanded beads are cut into approximately two equal parts passing through the center of the expanded beads, and a photograph is taken with a scanning electron microscope so that the entire surface of one of the cut surfaces is captured. Next, in the obtained cross-sectional photograph, 10 cells located near the center point C, which is approximately the center of the cut surface of the expanded beads, are selected. Note that the cells located near the center point C refer to cells located at the shortest position when the shortest straight line is drawn from the center point C to the cell membrane of the cells, and 10 cells are selected in order of the shortest straight line. In the cross-sectional photograph, a rectangle is drawn circumscribing the selected cells, and the average length of the vertical and horizontal lengths is measured. This is performed for all 10 selected cells, and the average value is taken as the cell diameter at the center of the expanded beads. This operation is performed in the same manner for 10 expanded beads, and the arithmetic average value of the cell diameters at the center of each expanded bead is taken as the average cell diameter Dc at the center of the expanded beads.
[0075] In addition, polyamide-based resin expanded beads having a closed cell rate of 80% or more and a ratio [Dc / D] of the average cell diameter Dc at the center of the expanded beads to the average cell diameter D of the entire expanded beads of 0.5 to 2.0 can be easily obtained by using hot air or an oil bath as a heating medium in the expansion process.
[0076] The expanded polyamide resin beads obtained according to the present invention can be used to produce an expanded polyamide resin bead molded article (hereinafter, also simply referred to as a molded article). The method for producing the molded body is not particularly limited, and can be any method known in the art.For example, the molded body is preferably produced by in-mold molding.In particular, the molded body is preferably produced by in-mold molding using steam, and according to this method, the polyamide resin constituting the polyamide resin foamed beads is plasticized by steam, so that the molding pressure during in-mold molding can be reduced. The obtained molded article has excellent lightness, and when dried, it is able to exhibit the inherent physical properties of the polyamide resin, resulting in a molded article having high heat resistance.
[0077] In addition, in the in-mold molding method, the method of filling the polyamide resin foamed beads into the mold can employ known methods. In consideration of the fusion property of the foamed bead molding, within a range that does not excessively increase the secondary foaming power of the foamed beads, the foamed beads are pressurized with a pressurized gas to impart a predetermined internal pressure to the bubbles of the foamed beads before being filled into the mold (pressurized pretreatment molding), the foamed beads are compressed with a pressurized gas and filled into the pressurized mold, and then the pressure in the mold is released (compression filling), and the foamed beads are opened in advance before filling the mold to expand the molding space, and the mold is closed after filling to mechanically compress the foamed beads (cracking filling), etc. can be employed.
[0078] The polyamide resin foamed bead moldings obtained by the method of the present invention have high heat resistance, excellent abrasion resistance, chemical resistance, etc., and also have excellent fusion properties and tensile strength of the moldings. Therefore, the moldings can be suitably used for automobile parts, electric appliances, etc. EXAMPLES
[0079] The present invention will be described in detail below with reference to examples, although the present invention is not limited thereto.
[0080] In the following Examples and Comparative Examples, the physical properties of the polyamide resin, polyamide resin particles, and expanded polyamide resin particles were measured by the following methods.
[0081] <Melting point of polyamide resin> The melting point of the polyamide resin was measured by heat flux differential scanning calorimetry based on JIS K7121-1987, by heating and melting the polyamide resin from 30°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min (first heating), then holding the temperature at that temperature for 10 minutes, cooling to 30°C at a cooling rate of 10°C / min, and again heating and melting the polyamide resin to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min. The melting point was measured as the temperature at the top of the melting peak of the second DSC curve (melting peak temperature). The measurement device used was a differential scanning calorimeter "EXSTAR DSC7020" (manufactured by SII Nano Technology Co., Ltd.). The polyamide resin was vacuum-suctioned in a desiccator under a nitrogen atmosphere to avoid hydrolysis under high temperature and high humidity conditions, and the polyamide resin was used for measuring the melting point.
[0082] <Aspect ratio l / d of resin particles> The aspect ratio l / d of the polyamide resin particles in a hygroscopic state was determined by measuring the maximum length l and the maximum cross-sectional diameter d of the cross-section of the resin particle in a direction perpendicular to the longitudinal direction of the maximum length for 50 randomly selected resin particles after the hydration process using a vernier caliper or the like, calculating the ratio l / d, and taking the arithmetic average of these values.
[0083] <Moisture content of resin particles> In the present invention, the moisture content of the polyamide resin particles was measured using a halogen moisture meter (HX204) manufactured by METTLER TOLEDO, which measures the moisture content based on heating with a halogen lamp. Specifically, first, the surface of the resin particles was wiped with Kimwipe manufactured by Nippon Paper Crecia Co., Ltd. to remove the moisture adhering to the surface of the resin particles, and about 2.0 g of polyamide-based resin particles were weighed and used as a measurement sample. Next, the measurement sample was heated to a temperature of 100°C using a halogen moisture meter device and maintained at 100°C for 60 seconds until the weight no longer changed, and then further heated to 160°C and maintained at 160°C for 90 seconds until the weight no longer changed, thereby vaporizing the moisture inside the test piece. The weight loss due to heating at this time was divided by the weight of the resin particles before heating and converted into a percentage to calculate the moisture content (%). The moisture content of the polyamide film described later was determined in the same manner as the moisture content of the polyamide-based resin particles, except that the weight of the test piece was about 0.5 g.
[0084] <Method for measuring the temperature at which the storage modulus of resin particles changes> The change point temperature of the storage modulus of the polyamide resin particles was determined based on the temperature change measured by dynamic viscoelasticity measurement (DMA, DMA7100 manufactured by Hitachi High-Tech Science Corporation) in accordance with JIS K7095:2012. First, a polyamide film of 100 mm length x 100 mm width x 0.4 mm thickness was prepared from the polyamide resin particles by compressing the polyamide resin particles with a heat press heated to 210 ° C. From this polyamide film, a film-shaped sample A (40 mm length x 50 mm width x 0.4 mm thickness) for determining the moisture content of the polyamide film and a film-shaped sample B (40 mm length x 5 mm width x 0.4 mm thickness) for measuring the change point temperature of the storage modulus of the polyamide film were cut out. The moisture content of the film-shaped sample A was measured by the above-mentioned method. The film-shaped sample B was fixed with a jig, and the temperature was raised from -80 ° C. to 130 ° C. at a heating rate of 2 ° C. / min in a tensile mode with a constant frequency (1 Hz) to measure the storage modulus. Then, as illustrated in FIG. 2, the measurement results were plotted to create a graph with the vertical axis representing the storage modulus and the horizontal axis representing the temperature. In the graph, the temperature indicated by a perpendicular line drawn downward from the intersection B between a straight line L1 extending to the high temperature side the straight line portion before the initial rapid drop in the storage modulus, and a straight line L2 extending to the low temperature side the straight line portion of the midpoint after the initial rapid drop in the storage modulus, was taken as the change-point temperature of the storage modulus. The measurement was carried out for 10 polyamide films previously adjusted to the same moisture content, and the arithmetic average value was taken as the change-point temperature of the storage modulus of the polyamide film at that moisture content.
[0085] The measurement was carried out using polyamide films made from multiple polyamide resin particles with different moisture contents, and the moisture content of the polyamide film was plotted on the horizontal axis and the storage modulus on the vertical axis to determine the relational equation between the moisture content and the change point of the storage modulus. This plot is shown in Figure 1. The obtained relational equation is shown in the following formula (1). y=-0.89x^3+2.3776x^2-23.146x+49.619...(1) however, y: Temperature at which the storage modulus of the polyamide resin particles changes (°C) x: Moisture content of polyamide resin particles (%) Thereafter, the temperature at which the storage modulus changes was calculated using the relational expression (1) from the value of the water content of the resin particles for which the temperature at which the storage modulus changes was to be calculated.
[0086] <Apparent density of expanded particles> Prepare a measuring cylinder containing water at 23°C and measure approximately 500 cm 3 The weight Wp of the polyamide resin foam particles in the dry state was measured, and the particles were submerged using a wire net. Taking into account the volume of the wire net, the volume Vp [cm 3 The weight Wp [g] of the expanded beads is divided by the volume Vp (Wp / Vp) and converted into units to obtain the apparent density [kg / m 3 ] was requested.
[0087] <Expansion ratio of expanded beads> First, dry expanded beads are placed in a measuring cylinder with a volume of 1 L, and a large number of expanded beads are placed up to the 1 L mark so that they are naturally piled up. The mass W2 [g] of the expanded beads is divided by the volume V2 (1 [L]) (W2 / V2) to convert the unit and obtain the bulk density [kg / m 3 Next, the density [kg / m 3 ] to the bulk density [kg / m 3 The expansion ratio of the expanded beads was calculated by dividing the expansion ratio by the expansion coefficient [times].
[0088] <Closed cell ratio of expanded beads> The closed cell ratio was determined using an air comparison type specific gravity meter based on procedure C described in ASTM-D2856-70. Specifically, it was determined as follows: Bulk volume: about 20 cm 3 The expanded beads in a dry state were used as a measurement sample, and the apparent volume Va was accurately measured by the ethanol immersion method as described below. After the measurement sample whose apparent volume Va had been measured was thoroughly dried, the true volume value Vx of the measurement sample was measured using an Accupyc II1340 manufactured by Shimadzu Corporation in accordance with procedure C described in ASTM-D2856-70. Based on these volume values Va and Vx, the closed cell ratio was calculated using the following formula (2), and the average value of five samples (N=5) was taken as the closed cell ratio of the expanded beads. Closed cell ratio (%)=(Vx-W / ρ)×100 / (Va-W / ρ) (2) however, Vx: The true volume of the foamed beads measured by the above method, i.e., the sum of the volume of the resin constituting the foamed beads and the total volume of the air bubbles in the closed cell part in the foamed beads (unit: cm 3 ) Va: The apparent volume of the foamed particles measured from the rise in the water level when the foamed particles are submerged in a measuring cylinder containing ethanol (unit: cm 3 ) W: weight of sample for foam particle measurement (unit: g) ρ: Density of the resin that composes the foamed particles (unit: g / cm 3 )
[0089] <Average bubble diameter D of expanded particles> First, the expanded beads in a dry state were cut into approximately two equal halves passing through the center of the expanded beads, and one of the cut surfaces was photographed with a scanning electron microscope so that the entire surface of the cut surface was captured. Next, in the obtained cross-sectional photograph, lines were drawn at 45° intervals in eight directions from near the center of the cut surface of the expanded beads, and the number of bubbles intersecting the lines was counted. The total length of the lines was divided by the number of bubbles counted to obtain the bubble diameter of the expanded beads. This operation was performed in the same manner for 10 expanded beads, and the arithmetic average value of the bubble diameters of each expanded bead was determined as the average bubble diameter D of the expanded beads.
[0090] <Average cell diameter Dc at the center of foamed beads, Dc / D> First, the expanded beads in a dry state were cut into approximately two equal parts passing through the center of the expanded beads, and a photograph was taken with a scanning electron microscope so that the entire surface of one of the cut surfaces was captured. Next, in the obtained cross-sectional photograph, 10 bubbles located near the center point C, which is approximately the center of the cut surface of the expanded beads, were selected. The bubbles located near the center point C refer to the bubbles located at the shortest position when a straight line is drawn from the center point C to the bubble membrane of the bubble, and 10 bubbles were selected in order of the shortest line. In the cross-sectional photograph, a rectangle was drawn circumscribing the selected bubbles, and the average values of the vertical and horizontal lengths were measured. This was performed for all 10 selected bubbles, and the average value was taken as the bubble diameter at the center of the expanded beads. This operation was performed in the same manner for 10 expanded beads, and the arithmetic average value of the bubble diameters at the center of each expanded bead was taken as the average bubble diameter Dc at the center of the expanded beads.
[0091] <Cross-section evaluation of expanded beads> The cross-section of the expanded beads was evaluated by first cutting the expanded beads in a dry state into approximately two equal halves, and taking a photograph of one of the cut surfaces using a scanning electron microscope so that the entire surface area of the cut surface was captured. From the cross-sectional photograph, the ratio of the area of the unfoamed portion to the total area of the cut surface was determined, and the evaluation was performed according to the following criteria. Note that the smaller the ratio of the area of the unfoamed portion, the more bubbles are formed throughout the entire cross section of the expanded beads, meaning that the foaming state is better. ◎: Unfoamed area is 10% or less ○: The area ratio of unfoamed parts is more than 10% and less than 25% ×: The area ratio of unfoamed parts is 25% or more.
[0092] Examples 1 to 5, Comparative Examples 1 to 3 [Production of polyamide resin particles] As a polyamide resin, polyamide 6 / 66 copolymer (polyamide 6 / polyamide 66 = 85 / 15; UBE nylon 5033B, manufactured by Ube Industries, Ltd., melting point 197°C, density 1.14 kg / m 3 , flexural modulus 1300MPa, MFR 3.5g / 10min) and "Talcan Powder PK-S" (manufactured by Hayashi Kasei Co., Ltd.) as a cell regulator was supplied so that the content was 8000 mass ppm, and "Stabaxol P" (manufactured by Rhein Chemie) as an end blocking agent was supplied so that the content was 1 part by mass, and the mixture was melt-kneaded, extruded into a strand shape, cooled in water, cut with a pelletizer so that the l / d was the value shown in the table, and dried to obtain polyamide-based resin particles with an average weight of 2 mg per particle. The obtained polyamide-based resin particles were dried at a temperature of 100°C and a humidity of 23% for 12 hours to obtain polyamide-based resin particles in a dry state. In addition, in the foaming process described later, Examples 1 to 3, Comparative Example 1, and Comparative Example 2 in which hot air was used as a heating medium are shown in Table 1, and Example 4, Example 5, and Comparative Example 3 in which steam was used as a heating medium are shown in Table 2.
[0093] [Hydrous process] The obtained polyamide-based resin particles in a dry state were used to adjust the moisture content. In Examples 1 and 4, the polyamide-based resin particles in a dry state obtained as described above were placed in a container containing water at a temperature of 15°C, and were completely immersed in the water for 1 hour, and then taken out, thereby adjusting the moisture content to the values shown in Tables 1 and 2. In Examples 2, 3, and 5, the obtained polyamide-based resin particles in a dry state were left to stand for 1 week at a temperature of 23°C and a humidity of 50%, thereby adjusting the moisture content to the values shown in Tables 1 and 2. In Comparative Examples 1 and 3, the moisture-imparting step was not performed. In Comparative Example 2, the obtained polyamide-based resin particles in a dry state were left to stand for 1 week at a temperature of 23°C and a humidity of 50% to adjust the moisture content, and then further dried for 1 hour at a temperature of 80°C and a humidity of 23%, thereby adjusting the moisture content to the values shown in Tables 1 and 2. The moisture content of the obtained resin particles and the change point temperature of the storage elastic modulus of the resin particles corresponding to the moisture content are shown in Tables 1 and 2.
[0094] [Foaming agent impregnation process] 180 g of the polyamide resin particles with the adjusted moisture content was placed in a 3 L pressure vessel set at the blowing agent impregnation temperature shown in Tables 1 and 2. Tables 1 and 2 also show the respective blowing agent impregnation temperatures, the change point temperatures of the storage modulus of the polyamide resin particles used, and the difference therebetween (impregnation temperature - change point temperature). The resin particles with the adjusted moisture content were placed in a pressure vessel and sealed, and at the same time, carbon dioxide was injected as an inorganic physical foaming agent to carry out the foaming agent impregnation step. The pressure (foaming agent impregnation pressure) of carbon dioxide as an inorganic physical foaming agent was kept constant at 4.0 MPa (G) in the pressure vessel. The foaming agent impregnation time (the time from when the inorganic physical foaming agent was injected until the expandable polyamide-based resin particles impregnated with the foaming agent were taken out of the pressure vessel) is shown in Tables 1 and 2. The foaming agent impregnation temperature was kept constant. Immediately after the foaming agent impregnation times shown in Tables 1 and 2 had elapsed, the expandable polyamide-based resin particles impregnated with carbon dioxide as an inorganic physical foaming agent were taken out of the pressure vessel.
[0095] [Foaming process] The foaming step was carried out as follows using expandable polyamide-based resin particles impregnated with carbon dioxide as an inorganic physical foaming agent. 180 g of expandable polyamide-based resin particles impregnated with carbon dioxide were heated by contact with a heating medium (expansion method) of a temperature and type shown in Tables 1 and 2 for a time shown in Table 1 to expand the expandable resin particles. The obtained expanded polyamide-based resin particles were cured in an oven at 80°C for 12 hours, and then slowly cooled to obtain dried expanded polyamide-based resin particles. Specifically, in an example where hot air was used as the heating medium, the particles were expanded by exposing the particles to a hot air medium at a temperature shown in Table 1 for a time shown in Table 1. In an example where steam was used as the heating medium, the particles were expanded by exposing the particles to a steam medium at a temperature shown in Table 2 for a time shown in Table 2.
[0096] The expanded beads in a dry state obtained as described above were measured for apparent density, closed cell ratio, and average cell diameter, and the results are shown in Tables 1 and 2. The cross section of the expanded beads was also observed, and the expansion state, such as the presence or absence of a core, was evaluated, and the results are shown in Table 1. In the examples in which steam was used as the heating medium, the closed cell ratio and average cell diameter were not measured, and cross section evaluation was not performed. In Comparative Examples 1 and 2, the expansion state was extremely poor, with many unexpanded parts, and measurement of the average cell diameter was difficult and therefore not performed.
[0097] [Table 1]
[0098] [Table 2]
[0099] (Example of hot air foaming) Example 1 is an example in which the moisture content of the resin particles in the foaming agent impregnation step was 14.9% by mass. The change point temperature of the storage modulus of the resin particles was -62°C, and the inorganic physical foaming agent could be impregnated into the resin particles under the impregnation conditions of 23°C and 24 hours, and foamed beads with a very good foaming state could be obtained by hot air foaming. A cross-sectional photograph of the foamed beads is shown in Figure 3. Example 2 is an example in which the water content of the resin particles in the foaming agent impregnation step was 4.3% by mass. The change point temperature of the storage modulus of the resin particles was -13°C, and the inorganic physical foaming agent could be impregnated into the resin particles under the impregnation conditions of 23°C and 24 hours, and expanded particles with a good foaming state could be obtained by hot air foaming. However, the foaming state was slightly inferior to that of Example 1. Example 3 is an example in which the same resin particles as in Example 2 were used, and the impregnation conditions were 50° C. and 3 hours. Compared to Example 2, the inorganic physical foaming agent could be impregnated into the resin particles in a short time, and expanded particles in a very good foaming state could be obtained by hot air foaming. Comparative Example 1 is an example in which the moisture content of the resin particles in the foaming agent impregnation step was 0.18% by mass. The storage modulus of the resin particles changed at a temperature of 46°C. When the resin particles were impregnated with an inorganic physical foaming agent at 23°C for 24 hours, the foaming state was extremely poor even after hot air foaming, and the foamed particles had a low closed cell ratio and many unfoamed portions. A cross-sectional photograph of the foamed beads is shown in Figure 4. Comparative Example 2 is an example in which the moisture content of the resin particles in the foaming agent impregnation step was 1.9% by mass. The storage modulus of the resin particles changed at a temperature of 14° C., and when the resin particles were impregnated with an inorganic physical foaming agent at 23° C. for 3 hours, the foaming state was extremely poor even after hot air foaming, and the foamed particles had a low closed cell ratio and many unfoamed portions.
[0100] (Example of steam foaming) Example 4 is an example in which expanded beads were produced in the same manner as in Example 1, except that steam was used as the heating medium. By steam expansion, expanded beads having a small apparent density could be obtained. Example 5 is an example in which expanded beads were produced in the same manner as in Example 2, except that steam was used as the heating medium. Expanded beads with a small apparent density could be obtained by steam expansion. However, the apparent density was larger than that of Example 4. Comparative Example 3 is an example in which expanded beads were produced in the same manner as in Comparative Example 1, except that steam was used as the heating medium. The resin beads were hardly expanded, and had a large apparent density. [Explanation of symbols]
[0101] L1: A straight line extending from the straight line section before the initial rapid drop in storage modulus to the high temperature side L2: A straight line extending from the mid-line to the lower temperature side after the initial rapid drop in storage modulus A. Temperature change vs. storage modulus curve B Intersection of lines L1 and L2
Claims
1. A method for producing expandable polyamide-based resin particles, comprising impregnating polyamide-based resin particles in a hygroscopic state having a water content of 2.5% by mass or more with an inorganic physical foaming agent in a gas phase.
2. 2. The method for producing expandable polyamide-based resin particles according to claim 1, wherein the polyamide-based resin particles in a moisture-absorbed state are impregnated with an inorganic physical foaming agent at a temperature higher than a temperature at which the storage modulus of the polyamide-based resin particles in a moisture-absorbed state changes.
3. 3. The method for producing expandable polyamide-based resin particles according to claim 2, wherein the temperature higher than the change point temperature of the storage elastic modulus is a temperature higher by 30°C than the change point temperature and 120°C or lower.
4. The method for producing expandable polyamide-based resin particles according to any one of claims 1 to 3, wherein the aspect ratio (l / d) of the polyamide-based resin particles in a hygroscopic state is 1.1 or more and 2.5 or less.
5. The method for producing expandable polyamide-based resin particles according to any one of claims 1 to 4, wherein the melting point of the polyamide-based resin constituting the polyamide-based resin particles in a hygroscopic state is 185°C or higher and 280°C or lower.
6. A method for producing expanded polyamide resin particles, comprising heating the expandable polyamide resin particles according to any one of claims 1 to 5 to expand them to obtain expanded polyamide resin particles.
7. The apparent density of the polyamide resin foam particles is 100 kg / m 3 More than 800kg / m 3 The method for producing expanded polyamide resin beads according to claim 6, wherein the method is as follows:
8. 8. The method for producing expanded polyamide resin beads according to claim 6, wherein the expanded polyamide resin beads have a closed cell rate of 80% or more, and a ratio [Dc / D] of the average cell diameter Dc at the center of the expanded beads to the average cell diameter D of the entire expanded beads is 0.5 or more and 2.0 or less.
Citation Information
Patent Citations
Foamed particle comprising polyamide resin
JP1995179645A
Polyamide resin foamed particle
JP2020059864A
Foamable resin particle and method for producing foamable resin particle
JP2021070713A
Polyamide-based resin foam particle
JP2021130739A
JPP6653049B